Market, public policies and producer cooperatives in the Uruguayan dairy at the beginning 20th century - Martí, Juan Pablo (Cooperativismo & Desarrollo, 2020)
In the first decades of the twentieth century, milk production began to develop in Uruguay. Although the antecedents refer to colonial times, it is only due to refrigeration techniques that milk production expanded and the number of producers decidedly increased. Producers cooperatives were essential for the development of dairy in Uruguay. The first of these was the Cooperativas de Lecherías Sociedad Anónima (COLE S.A.) which later gave rise to Conaprole, which became the industry leader and is currently the first Uruguayan exporting company. The creation of COLE S.A. came into being at the behest of dairy producers. On the other hand, for the creation of Conaprole the mobilization of dairy producers and public policies were combined. Conaprole is a particular case of a cooperative created by Law 9526 of 1935. This law, in addition to granting it a monopoly on the industrialization and commercialization of milk in the city of Montevideo, established a series of state intervention measures. This research probes into the reasons for the emergence of Conaprole. It analyzes the context of the time in its economic and social aspects, fundamentally noting the participation of dairy producers and their organizations. It also studies the political context, analyzing public policies and the ideas that were behind the creation of cooperatives and the evolution of the regulatory framework that led to the creation of Conaprole. Finally, it shows how the creation of Conaprole summarizes a process that draws on the mobilization of producers and the action of public authorities.